A delay‐rational model of electromagnetic interference on multiconductor transmission lines. (10th May 2018) - Biello, E.; Antonini, G.; De Lauretis, M.; Ekman, J.
Abstract: Multiconductor transmission lines have found a wide range of applications, as power lines, as high‐speed interconnects, and as on‐chip interconnects. Electromagnetic interference (EMI) can be described in terms of plane waves that couple to these lines, leading to unwanted disturbance. This paper presents a delayed spectral formulation for the analysis of plane‐wave coupling to multiconductor transmission lines in both the frequency and time domains, called the DeRaG‐EMI model (short for "delay‐rational model based on Green's functions for electromagnetic interference"). The model is based on Green's functions and is described in terms of delayed differential equations in the time domain. The model is suitable for studying the EMI on multiconductor transmission lines in the case of incident fields. The coupling of a plane wave to a line is described in terms of equivalent sources that account for both the delay of the line and the delays of the incoming plane wave. The delay is explicitly extracted and incorporated into the model with hyperbolic functions. The DeRaG‐EMI model does not require any segmentation of the line. Numerical results confirm its accuracy and its improved performance compared with the previous spectral model and with the inverse fast Fourier transform technique.